Bayesian Inference and Prediction of Wave-induced Ship Motion based on Discrete-frequency Model Approximations⁎. Issue 29 (2018) - Kennedy, Justin M.; Ford, Jason J.; Valentinis, Francis; Perez, Tristan
Abstract: In this paper, we investigate the use of a discrete-frequency approximation for stochastic processes, modelling wave-induced ship motion and assess its prediction performance. The proposed estimator is obtained by adapting Bayesian spectral inference methods. We study the relationship between the lag window and the prediction performance and suggest a minimum requirement on window length for minimising the prediction error. We show an application to prediction of the pitch, heave, and roll motion from experiments of a scale-model container ship.